INTERNET DEPENDENCY IN ADOLESCENTS: IMPLICATION FOR SCHOOL WORK PARTICIPATION AMONG SECONDARY SCHOOL STUDENTS IN RIVER STATE - Loveth Eguma, Nwabrije (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Because of the proliferation of internet technologies, which has been associated with internet addictions, more and more media reports indicate that most students no longer participate in activities associated with their education as much as they should. This trend may be hurting students' academic performance. The present study examined internet dependency as a variable that could account for the variations in schoolwork participation among secondary school students. Two hundred and fifty-two senior secondary school students from five public and private schools in River state participated in the survey. They completed a self-report measure of the Schoolwork Engagement Inventory and Smartphone Addiction Scale-Short Version (SAS-SV). The simple regression analysis conducted on the data revealed that internet dependency statistically significantly predicted the respondent's schoolwork participation F (1,250), 36.71, P<.000. Thus, the result affirmed the hypothesis that internet dependency would significantly correlate with schoolwork participation was supported. The practical implications and recommendations are discussed.